Smicridea mclachlan (Trichoptera: Hydropsychidae) from northwestern Argentina and bolivia: New species, redescription, association and new records - Rueda Martin, Paola Alejandra (2011)
Four new species of Smicridea (Rhyacophylax) are described from Argentina and Bolivia. Smicridea (Rhyacophylax) bifida sp. nov., S. (R.) elisae sp. nov. and S. (R.) valeni sp. nov. are described from the male; S. (R.) thermophyla sp. nov. is described as the first species of Smicridea from thermal springs. The larva and pupa of S. (R.) thermophila were associated using the metamorphotype method. New distributional records of S. (R.) dithyra, S. (R.) atrobasis, S. (R.) peruana and S. (R.) pampeana are included. Morphological characters of male S. (R.) peruana that were not mentioned before are included. Illustrations of all taxa named in this paper are included.